The effect of occlusal loading on cervical gap deformation: A 3D finite element analysis. Issue 5 (May 2020) - Hollanders, A.C.C.; Kuper, N.K.; Huysmans, M.C.D.N.J.M.; Versluis, A.
Graphical abstract: Abstract: Objectives: Secondary caries can be accelerated by hydrodynamic flow in a gap between the tooth and restorative material. This study investigated whether occlusal loading can lead to increased hydrodynamic flow by deforming a gap between tooth and restorative material. Methods: 3D finite element analysis was employed to model a molar containing a restoration with an interfacial gap. The model was loaded using direct cusp-to-restoration contact and using a rubber tube model simulating a food bolus. The object exerting pressure was moved across the molar from buccal to lingual side. The applied forces were 50, 100, 200 and 400 N. The elastic modulus of the restoration material was varied between 5, 10, 15.9 and 25 GPa to resemble different kinds of composite. The primary outcome parameter was the volume of the gap under occlusal pressure. Results: Occlusal loading resulted in deformation of the gap area. Maximum deformation was seen when loading was applied in the middle of the restoration. Higher forces and lower restoration stiffness led to more deformation of the gap. Maximum deformation with a force of 100 N and composite modulus of 15.9 GPa was −0.0083 mm 3 (1.12%). Significance: Deformation of the gap between tooth and restorative material could lead to increased hydrodynamic flow and faster secondary caries lesion formation. The measured deformation is small. Further research needs to show whether gap compression through occlusal loading affects secondary caries formation to a clinically relevant degree.